Peran Pengurus Wilayah Nahdatul Ulama Dalam Membumikan Islam Moderat Di Kota Kupang - Naitboho, Yanti Rosalina; Sari, Rahma Pramudya Nawang; Sali, Jakaria M.; Solo, Mohamad Idul Wegha; Arifin, Zainul (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
Absolute Moderate Islam has been explained in Q.S Al-Baqarah verse 145. This provision is arranged in accordance with the Decree of the Minister of Religion Number 93 of 2022 regarding the strengthening of religious moderation, which must be done in a directed, systematic, comprehensive, sustainable manner. , targeted and responsible way. The existence of religious moderation is based on strengthening the rights of the community in maintaining tolerance and, prospering community life, as well as preventing the emergence of religious conflicts. This research is a type of qualitative descriptive research with the collection of documentation data taken directly from the office of the District Manager of Nahdatul Ulama Timur Nusa Tenggara and interviews with the Nahdatul Ulama Timur Nusa Tenggara regarding the role that has been carried out and the Muslim and non-Muslim community as actors who respond to the impact of the application Moderate Islam on community life. Data processing through the stages of data inspection, classification, triangulation, data analysis, and conclusions. The results of this study found that the role of Nahdatul Ulama Regional Management in grounding Moderate Islam in the City of Kupang has been proven to be effective with the implementation of the vision and mission with supporting factors, namely the strengthening factor of Ukhuwah Islamiyah, the strengthening factor. Brotherhood of Insaniyah and factors that strengthen the relationship between religious leaders.